Correlating Stiffness and Shear Lag Behavior with Brace Configuration of Tall Truss Tube Buildings - Himanshu Gaur (Buildings, 2015)
As the height of buildings increases, effect of shear lag also becomes considerable in the design of high rise buildings. In this paper, shear lag effect in tall buildings of heights, i.e., 120, 96, 72, 48 and 36 stories of which aspect ratio ranges from 3 to 10 is studied. Tube in tube structural system with façade bracing is used for designing the building of height 120 story. It is found that bracing system considerably reduces the shear lag effect and hence increases the building stiffness to withstand lateral loads. Different geometric patterns of the bracing system are considered. The best effective geometric configuration of a bracing system is concluded in this study. Lateral force, as wind load, is applied on the buildings as it is the most dominant lateral force for such heights. Wind load is set as per Indian standard code of Practice IS 875 Part 3. For analysis purposes, the SAP2000 software program is used.